Histological variants of cutaneous Kaposi sarcoma - Pantanowitz Liron; Grayson Wayne (BMC, 2008)
Abstract This review provides a comprehensive overview of the broad clinicopathologic spectrum of cutaneous Kaposi sarcoma (KS) lesions. Variants discussed include: usual KS lesions associated with disease progression (i.e. patch, plaque and nodular stage); morphologic subtypes alluded to in the older literature such as anaplastic and telangiectatic KS, as well as several lymphedematous variants; and numerous recently described variants including hyperkeratotic, keloidal, micronodular, pyogenic granuloma-like, ecchymotic, and intravascular KS. Involuting lesions as a result of treatment related regression are also presented.